EFFECTS OF SHORT TERM PRACTICE OF BHASTRIKA PRANAYAMA ON METABOLIC FITNESS (METF) AND BONE INTEGRITY (BI) - Baljinder, Singh Bal (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: The present study was conducted with the objective to determine the short term practice of bhastrika pranayama on Metabolic Fitness and Bone Integrity. Material: 30 university level females between the age group of 21-26 years were selected. The subjects were randomly matched and assigned into two groups: Group-A: Experimental (n 1=15); Group-B: Control (n 2=15). The subjects from Group-A: Experimental were provided to a 4-weeks bhastrika pranayama. Statistical Analysis: Student t test for paired samples was utilized to compare the means of the pre-test and the post-test. Results & Conclusions: Based on the analysis of the results obtained, we conclude that the significant differences were found in Metabolic Fitness (i.e., Maximal Oxygen Consumption (V O2max) and blood pressure of University Level Girls. Insignificant between-group differences were noted in Blood Lipid, Blood Sugar and Bone Integrity of University Level Girls.